AB0241 After one Year of Treatment with Biologicals, "Newcomers" Achieve a Comparable Outcome as Patients on Long Lasting Treatment. Characteristics of Austrian Rheumatoid Arthritis Patients; one Year Follow up Data from Bioreg, the Austrian Registry for Biologicals. (9th June 2015) - Rintelen, B.; Herold, M.; Singer, F.; Hitzelhammer, J.; Zwerina, J.; Halder, W.; Eichbauer-Sturm, G.; Puchner, R.; Stetter, M.; Leeb, B.F.
Abstract : Background: BIOREG, the Austrian registry for patients (pts.) with chronic rheumatic diseases treated with biologic DMARD's, includes pts with rheumatoid arthritis (RA), spondylarthritis (SPA), psoriatic arthritis (PSA) and other diseases since 2010. Patients on biologic treatment are included irrespective of treatment duration and history. The primary interest of BIOREG is safety; aside disease activity, as well as socioeconomic data are documented. Objectives: The aim of this evaluation was to figure out eventual differences with respect to safety and disease activity in RA pts. on long term-biologics or new beginners on biologics after one year of treatment. Methods: RA pts. starting their first biologic treatment (NEW) and pts. treated with biologics for a longer time (LS) were compared with respect to demographic aspects, disease activity (DA) (DAS28, RADAI-5), HAQ-DI at baseline and after one year follow up (±3 months). Moreover, the percentages of remission (according to Boolean criteria (BC), to DAS28 and to RADAI-5) after the 1-year observation were calculated. Safety concerns were recorded. If not otherwise indicated median values, (first and third quartile) are given. Results: Two hundred and ninety pts. (257 LS, 33 NEW) of a total of 857 RA pts. were included into this evaluation as a full dataset was available. Disease duration amounted to 8.0 years (5.0, 13.0) for LS and 4.0 years (1.0, 9.0) for NEW pts., 78.5% were female, 81.8% respectively, the median age was 59.0 years (48.0, 67.0) and 57.0 (44.0, 70.0) respectively. LS were on biologic DMARDs since 3.05 years (1.47, 5.94). No difference in DA can be observed after 1 year according to the DAS28 (LS 2.60 (1.81, 3.43) and NEW 2.41 (1.54, 3.28)), the RADAI-5 (LS 2.2 (1.0, 4.0) and NEW 2.4 (1.0, 3.8)), BC (LS 24.9% vs NEW 24.2%), DAS28 remission (50.6% vs 57.6%), RADAI-5 remission (36.2% vs 30.3%) respectively. Likewise, no difference in HAQ-DI-scores after one yearcould be observed. Forty-eight adverse events had to be noticed in the LS pats (22%) and 15 in the NEW pats (46%) most likely infections. Malignant diseases occurred in 4 pats (3 LS and 1 NEW). Conclusions: After 1 year of biologic treatment all pts. achieve a comparable level of disease activity control. Adverse events occur more frequently during the early phase of biologic treatment. Disclosure of Interest: B. Rintelen Grant/research support from: BIOREG is supported by an industrial grant, M. Herold Grant/research support from: BIOREG is supported by an industrial grant, F. Singer Grant/research support from: BIOREG is supported by an industrial grant, J. Hitzelhammer Grant/research support from: BIOREG is supported by an industrial grant, J. Zwerina Grant/research support from: BIOREG is supported by an industrial grant, W. Halder Grant/research support from: BIOREG is supported by an industrial grant, G. Eichbauer-Sturm Grant/research support from: BIOREG is supported by an industrial grant, R. Puchner Grant/research support from: BIOREG is supported by an industrial grant, M. Stetter Grant/research support from: BIOREG is supported by an industrial grant, B. Leeb Grant/research support from: BIOREG is supported by an industrial grant